The Role of Reading Books in Shaping Youth Spirituality (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The article examines the influence of book reading on the formation of spiritual values and worldviews among young people. Particular attention is paid to the cultural and educational functions of literature, its role in developing critical thinking, moral consciousness, and personal growth. Examples of works contributing to spiritual development are provided, and the issue of declining interest in reading in modern society is analyzed.